Mechanical characterization of new geopolymeric materials based on mining tailings and rice husk ash - Huamán-Mamani F.A. (2021)
This work presents the results of the thermomechanical evaluation of geopolymeric concrete fabricated from mining tailings, rice husk ash and fine sand. Ten types of geopolymeric concrete were studied and the relationship between the initial volumetric concentrations of the components in the mixtures and the maximum resistance in uniaxial compression under conditions of variable temperature (between ambient and 600 ºC) was analyzed. The results revealed that increases in the concentration of mining tailings and fine sand lead to an increase in the value of the maximum mechanical resistance, in contrast, the increase in the concentration of rice husk ash led to a reduction in the value of the maximum mechanical resistance. Furthermore, increases in test temperature, up to 500 °C, led to systematic increases in maximum mechanical strength. Finally, the geopolymeric concretes presented a brittle-ductile transition between 500 and 600 °C showing only a ductile behavior when tested at 600 °C and only brittle up to test temperatures of 500 °C.